The Effect of Differential Weighting of Academics, Experiences, and Competencies Measured by Multiple Mini Interview (MMI) on Race and Ethnicity of Cohorts Accepted to One Medical School. (December 2015) - Terregino, Carol A.; McConnell, Meghan; Reiter, Harold I.
Abstract : Purpose: To examine whether academic scores, experience scores, and Multiple Mini Interview (MMI) core personal competencies scores vary across applicants' self-reported ethnicities, and whether changes in weighting of scores would alter the proportion of ethnicities underrepresented in medicine (URIM) in the entering class composition. Method: This study analyzed retrospective data from 1, 339 applicants to the Rutgers Robert Wood Johnson Medical School interviewed for entering classes 2011–2013. Data analyzed included two academic scores—grade point average (GPA) and Medical College Admission Test (MCAT)—service/clinical/research (SCR) scores, and MMI scores. Independent-samples t tests evaluated whether URIM ethnicities differed from non-URIM across GPA, MCAT, SCR, and MMI scores. A series of "what-if" analyses were conducted to determine whether alternative weighting methods would have changed final admissions decisions and entering class composition. Results: URIM applicants had significantly lower GPAs ( P < .001), MCATs ( P < .001), and SCR scores ( P < .001). However, this pattern was not found with MMI score (non-URIM 10.4 [1.6], URIM 10.4 [1.3], P = .55). Alternative weighting analyses show that including academic/experiential scores impacts the percentage of URIM acceptances. URIM acceptance rate declined from 57% (100% MMI) to 43% (10% GPA/10% MCAT/10% SCR/70% MMI), 39% (30% GPA/70% MMI), to as low as 22% (50% MCAT/50% MMI). Conclusions: Sole reliance on the MMI for final admissions decisions, after threshold academic/experiential preparation are met, promotes diversity with the accepted applicant pool; weighting of "the numbers" or what is written about the application may decrease the acceptance of URIM applicants.